In vitro Analysis of Heavy Metal Interference in Immune System of Estuarine Black Clam Villoritta cyprinoides (Gray) - Unnikrishnan, Likhija; Tomson, Majesh; P, Rajiv; D, Vidhya; Nair, Balu M (Asian Journal of Biological and Life Sciences)
Deposition of metals in aquatic organisms leads to a long-standing burden on biogeochemical cycling in the environment. Bioaccumulation of heavy metals becomes an environmental problem, when chemicals accumulated are poisonous. Toxicity may take place along the food chain when the infected species or a material is consumed. In this study we exposed the clams with sublethal concentration of cadmium and lead, and analyzed the consequence of heavy metals on immune molecules, viability, hemocyte count, some important enzymes and DNA damage of the cell. After analysing the heavy metals in V. cyprinoides, two heavy metals Cadmium and Lead were selected for the supplementary studies as per the AAS analysis. Metals were tested its sublethal concentration after the exposure of 24 hr in laboratory condition. Lethal and sublethal concentrations of cadmium and lead were determined after the acclimatization of clams. Three replicates were done and the 24 hr LC50 value was recorded and statisticaly analysed. The sublethal concentration (Cd 0.030 ppm and Pb 0.020 ppm) of heavy metals also were recorded. The activity of agglutinin molecule in the serum of heavy metal treated V. cyprinoides is one fold lesser than the non-treated animal and the lethal concentration of Cd and Pb affect the activity of agglutinin molecule.
Keywords: Bioaccumulation; Black clam; Heavy metals; Immune response; Villoritta cyprinoides